2018
DOI: 10.1002/fee.1809
|View full text |Cite
|
Sign up to set email alerts
|

Fish‐smart seawalls: a decision tool for adaptive management of marine infrastructure

Abstract: Infrastructure is increasingly being built in marine habitats, with extensive ecological consequences for benthic and fish assemblages alike. The practice of ecological engineering attempts to mitigate the negative impacts of infrastructure through the design of artificial structures that benefit both humans and nature. Although research has primarily focused on the benefits for invertebrates and algae, fish also respond to changes in habitat complexity and benthic biodiversity. We surveyed the scientific lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Manmade (artificial) reefs have long been used as a successful option for restoration of marine ecosystems (Bohnsack and Sutherland, 1985;Bohnsack et al, 1994). Many hard substrates create manmade reefs, from purposefully designed quarry rock structures to breakwalls, pier pilings, and even sunken shipwrecks (Morris et al, 2018). When standardized, comparisons with natural reefs suggest that manmade reefs can sustain similar levels of species richness and abundance (Carr and Hixon, 1997;Pondella et al, 2002Pondella et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Manmade (artificial) reefs have long been used as a successful option for restoration of marine ecosystems (Bohnsack and Sutherland, 1985;Bohnsack et al, 1994). Many hard substrates create manmade reefs, from purposefully designed quarry rock structures to breakwalls, pier pilings, and even sunken shipwrecks (Morris et al, 2018). When standardized, comparisons with natural reefs suggest that manmade reefs can sustain similar levels of species richness and abundance (Carr and Hixon, 1997;Pondella et al, 2002Pondella et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In Arctic regions, ice‐road construction associated with oil and gas development sites has potential to disturb hydrological connectivity to important seasonally accessible lakes and streams during the summer (Arp et al, ). In marine environments, seawalls are being built at unprecedented rates that may eliminate or prevent access to the intertidal zone (Morris et al, ).…”
Section: The Capacity Of Aquatic Ecosystems To Support Fishmentioning
confidence: 99%
“…Augmentation of flows beyond natural levels disturbs natural processes of drying and freezing, and changes phenology that may lead to the proliferation of non‐native species that have distinct ecological advantages in stable conditions. Additionally, maintaining access to TAHs that serve functional roles will be increasingly important as roads fragment dendritic riverscapes and seawalls limit intertidal zone access (Morris et al, ).
The fact that rare or unique features in riverscapes can be disproportionately important to stream fish emphasizes the need for judicious use of continuous sampling in space and time. (Fausch et al, )
…”
Section: The Big Picture: Research Needs and Resource Managementmentioning
confidence: 99%
“…Recently, efforts to enhance the diversity on coastal defence structures showed that structures such as seawalls and breakwaters could be modified in an attempt to increase the biodiversity they support. This has included the addition of simple topographic features such as pits, grooves, cracks or water‐retaining structures (Browne & Chapman, ; Chapman & Blockley, ; Coombes et al, ; Dafforn et al, ; Dafforn, Mayer‐Pinto, Morris, & Waltham, ; Evans et al, ; Firth, Browne, Knights, Hawkins, & Nash, ; Firth, Mieszkowska, et al, ; Firth, Schofield, White, Skov, & Hawkins, ; Firth, Thompson, et al, , ; Martins, Thompson, Neto, Hawkins, & Jenkins, ; Morris, Chapman, Firth, & Coleman, ; Morris et al, ; Strain et al, for a review). In order to further increase their ecological value, we need to understand how modifications made to coastal defence structures might affect species coexistence with potential long‐lasting effects (Martins, Jenkins, Neto, Hawkins, & Thompson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts to enhance the diversity on coastal defence structures showed that structures such as seawalls and breakwaters could be modified in an attempt to increase the biodiversity they support. This has included the addition of simple topographic features such as pits, grooves, cracks or water-retaining structures (Browne & Chapman, 2014;Chapman & Blockley, 2009;Coombes et al, 2015;Dafforn, Mayer-Pinto, Morris, & Waltham, 2015;Evans et al, 2015;Firth, Browne, Knights, Hawkins, & Nash, 2016;Firth, Mieszkowska, et al, 2013;Firth, Schofield, White, Skov, & Hawkins, 2014;, 2014Martins, Thompson, Neto, Hawkins, & Jenkins, 2010;Morris, Chapman, Firth, & Coleman, 2017;Morris et al, 2018;Strain et al, 2018 for a review).…”
mentioning
confidence: 99%